Some Observations on the Stink-bug, Cyclopelta siccifolia (Westw.) (Heteroptera : Pentatomidae), a Pest of Butea monosperma (lam.) O. Ktze. - Varshnev, R. K. (Indian Forester, 1967)
Cyclopelta siccifolia (Westw.) is pest on many economic plants. It is reported here as a pest on Butea monosperma. Notes on morphology and biology of the bug are given.